Raw Material Control for Chicken Crumble Feed Production: Pengendalian Bahan Baku untuk Produksi Pakan Ayam Crumble - Wijatmiko, Erie Fadma Noer Fitriana; Sukmono, Tedjo (Procedia of Engineering and Life Science, 2024)
Raw materials are essential for production, sourced from natural reserves or acquired from suppliers. Material Requirement Planning (MRP) is a vital method for managing material demand, utilizing inventory, forecasts, and production schedules. This study addresses the importance of inventory control and MRP in ensuring adequate raw material supply for production. The research aims to analyze MRP calculations to determine the required raw material quantities over a specified period. By employing MRP, production planners can efficiently order raw materials to prevent shortages or excessive inventory. The results highlight the significance of MRP in optimizing inventory management and ensuring uninterrupted production. Highlights : MRP ensures efficient raw material management. Study analyzes MRP calculations for required quantities. Results emphasize MRP's role in optimizing inventory and production. Keywords : Raw materials, Material Requirement Planning (MRP), inventory control, production scheduling, uninterrupted production